2022
DOI: 10.1111/iep.12460
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of RhoC induces macrophage M1 polarization to inhibit migration and invasion in colon cancer via regulating the PTEN/FOXO1 pathway

Abstract: Ras homologue family member C (RhoC) is an oncogene in diverse types of human cancers, whereas its regulatory mechanisms involving macrophage polarization is rarely investigated. This study is designed to explore the regulatory role of RhoC in colon cancer and the underlying molecular mechanisms involving macrophage polarization. We detected RhoC expression by quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blot, and analysed the biological function of RhoC knockdown in CC cells by the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This process leads to the suppression of TLR4 expression, thereby inhibiting the polarization of M2 macrophage. 46,47 The WU study showed that in mice with periodontitis, PTEN were more prominent than in other species. In mice with periodontitis, PTEN expression was significantly higher than in controls, and high PTEN expression promoted classical macrophage polarization (M1 polarization).…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
“…This process leads to the suppression of TLR4 expression, thereby inhibiting the polarization of M2 macrophage. 46,47 The WU study showed that in mice with periodontitis, PTEN were more prominent than in other species. In mice with periodontitis, PTEN expression was significantly higher than in controls, and high PTEN expression promoted classical macrophage polarization (M1 polarization).…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%